2022
DOI: 10.11591/ijeecs.v26.i1.pp229-242
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive neuro-fuzzy controller trained by genetic-particle swarm for active queue management in internet congestion

Abstract: Routers are vital during network congestion. All routers have input and output packet buffers. V<span lang="EN-US">Various congestion control strategies have been suggested. Some controller-based proportional-integral derivative (PIDs) have recently been offered as active queue management (AQM) solutions to alleviate the deterioration of transmission control protocol (TCP) congestion management system performance. However, the time delay is large, the data retention decreases, and oscillation occurs, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…To start simulation for controlling temperature in greenhouse we must specify the desired temperature needed, in this study 25 o C is regarded as an optimal value for the greenhouse environment and based on this the controller with the smart GTO optimization method will track the and monitoring the response to reach to the desired value with a stable behavior, all simulation results is obtained using MATLAB 2019 and the parameter of the GTO algorithm is shown in Table 1. The system error between desired and actual response is monitored and minimized using ITAE function [26], [27] as shown in (18) in the smart GTO algorithm iterations, Figure 5 The system response is indicated in Figure 6 and for demonstrate the controller efficiency a comparison with two conventional controller (PI and PID) is done and the response of all controllers is shown in Figure 7, and all controllers gain values is shown in Table 2. The response analysis results for the comparison of all controllers are shown in Table 3.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To start simulation for controlling temperature in greenhouse we must specify the desired temperature needed, in this study 25 o C is regarded as an optimal value for the greenhouse environment and based on this the controller with the smart GTO optimization method will track the and monitoring the response to reach to the desired value with a stable behavior, all simulation results is obtained using MATLAB 2019 and the parameter of the GTO algorithm is shown in Table 1. The system error between desired and actual response is monitored and minimized using ITAE function [26], [27] as shown in (18) in the smart GTO algorithm iterations, Figure 5 The system response is indicated in Figure 6 and for demonstrate the controller efficiency a comparison with two conventional controller (PI and PID) is done and the response of all controllers is shown in Figure 7, and all controllers gain values is shown in Table 2. The response analysis results for the comparison of all controllers are shown in Table 3.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…PID controllers are classified as an easy and traditional controllers adopted for improving the performance of the system. Nowadays, many studies suggested different modifications and structures for more enhancement in system response either by combining PID controller with some intelligent methods such as neural network [17] or using fuzzy logic with it [18] or modify its structures based on system behavior as in [19], [20] or adopt the fractional analysis either the integral or the differential parts of PID controller or together by fraction number for improving system response, this form of enchantment is a special case controller and become an improved structure of conventional PID controller [21]. In this paper, a novel cascade structure named proportional-integral-one plus integral-derivative PI-(1+ID) [22] is suggested to control temperature based o GTO algorithm and its block diagram is shown in Figure 3.…”
Section: The Proposed Controllermentioning
confidence: 99%
“…The ITAE function is considered as a fitness function to test the error continuously [27], the behavior of the ITAE fitness function for the optimal backstepping controller is is shown in Figure . 4. The system response using optimal backstepping controller is shown in Figure 5 and the gain of these two controllers is also tuned using SSA tuning algorithm and shown in Table 3, a comparison with two conventional controllers (PI &PID) is done to show the effectiveness of the proposed controller based on transient response analysis as indicated in Table 4.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Another extension of this study could be to implement the proposed controller in a real-time environment, either using LabVIEW programming software or using other embedded hardware designs such as FPGA or Raspberry Pi [46]. Other control techniques could be suggested to conduct a comparison study for this medical application [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%